Improved BioGents® Sentinel trap with heat (BGSH) for outdoor collections of Anopheline species in Burkina Faso and Mali, West Africa - Guindo, Amadou; Epopa, Patric Stephane; Sidy Doumbia, Sidy (Parasites Vectors, 2021)
Background: Since the late 1990s, malaria control programmes have relied extensively on mass bednet distribution and indoor residual spraying. Both interventions use pesticides and target mosquitoes coming indoors either to feed or to rest. Unfortunately, these intensified vector control campaigns have resulted in mosquito populations with high levels of resistance to most of the chemical compounds used against them and which are increasingly exophagic and exophillic, hence difficult to monitor indoors. Consequently, there is an urgent need for novel tools to sample outdoor anopheline populations for monitoring interventions and disease surveillance programmes. Methodologies: In this study, we tested several modifications and configurations of the BioGents® Sentinel (BGS) trap, designed with the aim to increase its efficacy for sampling malaria vector species. Traps were used with chemical attractants and CO2, and the impacts of trap position, trap colour contrast combination and the addition of a heat source were tested in two studies conducted in the Sudano-Sahelian region of Burkina Faso and Mali. Results: The results show that of all the configurations tested, the addition of a heat source to the BGS trap with the original colour combination and an upward positioning resulted in a 1.8- and 5.9-fold increase in host-seeking Anopheles gambiae (s.l.) females in the experiments performed in Burkina Faso and Mali, respectively. BGS with heat traps, referred to as BGSH traps, captured An. gambiae (s.l.), An. pharoensis, An. coustani, Culex and Mansonia spp. Importantly, the results suggest that their efficacy does not depend on the close proximity of nearby hosts in houses. Conclusions: The results suggest that BGSH traps can be an effective scalable tool for sampling outdoor anopheline vector populations. Further developments enabling CO2 and heat generation for longer periods of time would further improve the trap's versatility for large-scale surveillance programmes.
Keywords: Anopheles gambiae (s.l.); Counter-flow traps; Exophagy; Heat attraction; Host-finding; Malaria; Outdoor biting; Surveillance.; Abdoul‑Azize Millogo; Brehima Diallo; ACE: Bio-technological Innovation for the Elimination of Vector- Borne Diseases; CEA-ITECH_MTV; Université Nazi Boni